Effects Of Exercise Regimens On Down Syndrome Patients' Cardiovascular Responses: A Systematic Review - Ayudhia; Ivanna (The Indonesian Journal of General Medicine, 2024)
Background: Low cardiovascular fitness is common in Down syndrome (DS) patients, with VO2peak values consistently lower compared to peers without disabilities and those with intellectual disabilities. Regular physical activity is crucial for maintaining general health and preventing chronic diseases. Strategies for improving cardiorespiratory fitness in DS include aquatic training, water-based exercises, aerobic training, and plyometric training. Methods: The author followed PRISMA 2020 guidelines for a systematic review of randomized controlled trials aimed at improving cardio-vascular parameters through exercise interventions. Result: The study analyzed twelve exercise regimens for Down syndrome individuals, with an average training period of 15 weeks. Results showed consistent and stable results, but did not significantly improve HRpeak, VO2peak, RER, time to exhaustion, or peak minute ventilation. Conclusion: Down syndrome patients often struggle with reduced exercise capacity, leading to reduced survival rates. Cardiovascular exercise programs can increase workload, peak oxygen consumption, and time to exhaustion. However, exercise may not significantly impact heart rate due to less hormonal responses. Designing breathing-friendly exercise programs can improve respiratory function.